Edmodo Based Blended Learning Model Employed In Comprehending Reading Text - Wibowo, Amiruddin Hadi; Ulfaika, Romlah (Jurnal Borneo Humaniora, 2022)
The use of Edmodo-based blended learning in reading comprehension at Surabaya Merchant Marine Polytechnic. This study used both online and offlineÂ lectures. Edmodo was used by students and lecturers in online lectures. Students and lecturers discussed the topics they have seen and studied at homes. This learning model is preferred by students. This study used three instruments: participant observation, in-depth interview, and questionnaire. The study's subjects were lecturers and students at Merchant Marine Polytechnic of Surabaya. The results showed an intensity and quality of student to student and student-lecturer interactions. The students preferred the Edmodo-based blended learning model. The workload for students is moderate. Thus, the Blended Learning model operates well in reading comprehension classes.Â Keyword; Edmodo, Blended Learning, Reading Comprehension